Plasma-derived exosomes implement miR-126-associated regulation of cytokines secretion in PBMCs of CHF patients in vitro - Natrus, Larysa; Labudzynskyi, Dmytro; Muzychenko, Petro; Chernovol, Petro; Klys, Yuliia (Acta Biomedica Atenei Parmensis, 2022)
Background The investigation of regulatory effects of intra-exosomal compounds, especially microRNAs, has promising therapeutic prospects in the treatment of numerous diseases, including cardiovascular disorders. In this study, we investigated the effect of healthy donors` plasma exosomes (HDPE) on the production of cytokines by PBMC cells of patients with congestive heart failure (CHF) and showed the integral role of miRNA-126 in CHF-mediated changes of mononuclear paracrine secretion. Methods Peripheral blood mononuclear cells (PBMСs) were isolated from a peripheral blood of fifteen patients with CHF (age, 66,8±9,8 years; left ventricular ejection fraction, 44±19%). The concentration of cytokines (IL-10, ICAM-1, VEGF-A, TNF-α and MCP-1) in culture medium and PBMCs was measured by ELISA. The level of miRNA-126 expression in PBMCs was performed by real-time PCR. Results Dramatic increase of ICAM-1 level in activated PBMCs of CHF patients, as well as an increase of the IL-10, ICAM-1 and TNF-α levels in the culture medium was observed. It was accompanied by CHF-related miRNA-126 overexpression in PBMCs. HDPE treatment distinguished by a tendency to reduction in miRNA-126 expression by CHF PBMCs and correlated with upregulation of IL-10, ICAM-1, TNF-α and MCP-1 with normalization of cytokines secretion. Conclusions The altered paracrine secretion of cytokines by CHF PBMCs and miRNA-126 overexpression in vitro was found. HDPE treatment modulated production and secretion of most of studied cytokines by CHF PBMCs in vitro. The experimental application of exosomes for the modulation of paracrine secretion and PBMCs cellular functions may be promising for CVD therapy, including endothelial dysfunction and CHF.